Fractionation and Identification of Java Plum Fruit (Syzygium cumini) Extract - Lydia Ninan Lestario; Sri Raharjo; Suparmo Suparmo; Pudji Hastuti; Tranggono Tranggono (Indonesian Food and Nutrition Progress, 2004)
Java plum (Syzygium cumini} fruit is a tropical, purple fruit that has a potency as a source of natural antioxidant. The objective of this study were to investigate further about the stability of the fruit extract towards pH and UV exposure, to separate the fruit extract by column chromatography filled with silica gel G-60 to its components and to determine as well as to identify which component had highest antioxidant activity. The results showed that the fruit extract was red, orange, yellow, brown, and purple, and blue colors at pH 1-3, 4, 5, 6, 7, and 8 respectively. Among those colors, red had high stability toward low wavelength UV exposure (254 nm) up to 3 hours. The very low degree on slope of the regression line indicated that the fruit extract was particularly stable toward UV light. Separation of the fruit extract by column chromatography filled with silica gel G-60, and followed by gradient elution with EtOAc and MeOH/H20 (1:1) resulted in five fractions including : three were colorless and two were red and pink respectively. The red fraction, however contained anthocyanin and had highest antioxidant activity. The red fraction were then identified by paper chromatography and TLC both ascrude (without hydrolisis) and as acid hydrolyzed extracts. The crude extract used BAW, Bu-HCl, and HCl 1% as developing solvents; whereas hydrolyzed extract used forestal and formic as developing solvents. Anthocyanidin standards were spotted together with the hydrolyzed extract. The identification was based on the Rf values, color of spots visible and under UV light. The results of the hydrolyzed extract showed that there were three spots identified as : pelargonidin, cyanidin, delphinidin; while the non hydrolized extract showed three spots which were identified as : pelargonidin 3-(p-coumaryl-glucoside)- 5glucoside, cyanidin 3-glucoside, and delphinidin 3-rhamnosilglucoside.